Man's 4th best hospital - Shem, Samuel (Berkley, 2019)
The sequel to the bestselling and highly acclaimed The House of God. One of the most prominent and enduring titles in medical fiction is the bitingly funny House of God, which has sold more than 2 million copies, becoming required reading for generations of medical students and health care professionals. With Man's 4th Best Hospital, Samuel Shem "the comic genius and holy terror of medicine"* returns us to the hilarious and heartbreaking world of modern medicine. After The House of God, the resident known as The Fat Man and his eccentric band of interns scattered to the four corners of the country. Today Fats, now rich and famous, has been lured across town to the House of God's WASPy rival, Man's Best Hospital. But the august institution has sunk from being ranked the best hospital in the country to an embarrassing, and unacceptable, 4th! Fats' mission? To help the hospital climb back up the rankings. But as always, he's pursuing his own agenda. . . At his new Future of Medicine Clinic, the team comes back together to renew their life-changing friendships and teach a new generation of interns and residents. In a medical landscape dominated by computer screens and corrupted by money, they have a daunting goal: "To put the human back into healthcare." What follows is an emotional and laugh-out-loud novel that reflects the issues in American healthcare today, from the tyranny of computer screens to doctor burnout to the greed of the health insurance industry. * Bill McKibben